Lymphocyte cytosolic protein 2 is a novel prognostic marker in lung adenocarcinoma - Yishan Huo (SAGE Publishing, 2021)
Objective Lymphocyte cytosolic protein 2 (LCP2) is often ectopically expressed in various human tumors. However, the clinical significance and role of LCP2 in lung adenocarcinoma (LUAD) remain unclear. This study explored the prognostic significance of LCP2 in LUAD patients. Methods LCP2 expression in LUAD tissues was analyzed using data from The Cancer Genome Atlas and Genotype-Tissue Expression databases. Western blotting was employed to detect LCP2 expression in LUAD. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses were performed to explore signaling pathways mediated by LCP2 co-regulatory genes. Immunohistochemistry was used to examine levels of LCP2 and programmed death ligand 1 (PD-L1) in 68 LUAD patients. Associations between LCP2 expression and clinicopathological features, prognoses, and PD-L1 levels among the LUAD in-patients were analyzed. Results Among the 68 LUAD in-patients, LCP2 expression was correlated with clinical stage and lymph node metastasis. LUAD patients with high LCP2 expression were associated with increased overall survival. LCP2 expression may be associated with an enrichment of several immune functions. Moreover, our immunohistochemistry results demonstrated that LCP2 expression was positively correlated with PD-L1 expression in LUAD tissues. Conclusions In the study, LCP2 was found to be a favorable prognostic biomarker in LUAD patients.